Dynamically Cyclic Fe2+/Fe3+ Active Sites as Electron and Proton-Feeding Centers Boosting CO2 Photoreduction Powered by Benzyl Alcohol Oxidation - Ben Lei; Gaofeng Zhou; Zhongyou Gong; Chao Liu; Ying Zhou; Vitaliy P. Guro; Yanjuan Sun; Jianping Sheng; Fan Dong (Research)
Solar-driven CO2 photoreduction holds promise for sustainable fuel and chemical productions, but the complex proton-coupled multi-electron transfer processes and sluggish oxidation half-reaction kinetics substantially hinder its efficiency. Here, we devised a rational catalyst design to address these challenges by fabricating ferrocene carboxylic acid-functionalized Cs3Sb2Br9 nanocrystals (CSB-Fc NCs), which facilitate simultaneous benzyl alcohol oxidation and CO2 reduction reactions under visible-light irradiation. The synchronized proton-coupled electron transfer processes between the reduction and oxidation half-reactions on CSB-Fc NCs resulted in a 5-fold increase in the CO2 reduction rate (45.56 μmol g−1 h−1, 97.9% CO selectivity) and a 5.8-fold enhancement in benzyl alcohol conversion (97.7% selectivity for benzaldehyde) compared to the CSB. In situ Raman and ultraviolet-visible diffuse reflectance spectra revealed that the dynamic Fe2+/Fe3+ redox loop within the Fc unit serves as the actual active site, facilitating the activation of substrate molecules. More importantly, in situ attenuated total reflection Fourier transform infrared spectroscopy and gas chromatography–mass spectrometry spectroscopy, with isotope labeling of Deuteron-benzyl alcohol and 13CO2, confirmed that proton transfer from the hydroxyl group generates reactive protons at the Fe2+/Fe3+ site, enabling efficient CO2 photoreduction through subsequent protonation steps. This work offers a cost-effective and efficient approach for synergetic CO2 photoreduction driven by organic synthesis, advancing solar energy utilization.